A Catalase‐Like Metal‐Organic Framework Nanohybrid for O2‐Evolving Synergistic Chemoradiotherapy. (16th May 2019) - He, Zhimei; Huang, Xiaolin; Wang, Chen; Li, Xiangli; Liu, Yijing; Zhou, Zijian; Wang, Sheng; Zhang, Fuwu; Wang, Zhantong; Jacobson, Orit; Zhu, Jun‐Jie; Yu, Guocan; et al.
Abstract: Tumor hypoxia, the "Achilles' heel" of current cancer therapies, is indispensable to drug resistance and poor therapeutic outcomes especially for radiotherapy. Here we propose an in situ catalytic oxygenation strategy in tumor using porphyrinic metal‐organic framework (MOF)‐gold nanoparticles (AuNPs) nanohybrid as a therapeutic platform to achieve O2 ‐evolving chemoradiotherapy. The AuNPs decorated on the surface of MOF effectively stabilize the nanocomposite and serve as radiosensitizers, whereas the MOF scaffold acts as a container to encapsulate chemotherapeutic drug doxorubicin. In vitro and in vivo studies verify that the catalase‐like nanohybrid significantly enhances the radiotherapy effect, alleviating tumor hypoxia and achieving synergistic anticancer efficacy. This hybrid nanomaterial remarkably suppresses the tumor growth with minimized systemic toxicity, opening new horizons for the next generation of theranostic nanomedicines. Abstract : Ein Katalase‐ähnlicher Nanohybrid auf Basis von AuNPs/Gold(III) porphyrinischen Metall‐organischen Gerüsten wird für die O2 ‐entwickelnde Radiochemotherapie hergestellt. Ein solcher All‐in‐One‐Nanohybrid bietet die Vorteile der Tumorhypoxie‐Modulation, der Strahlenwirkungsverstärkung, der Regulierung der Wirkstofffreisetzung und der Kombination von Chemotherapie mit Strahlentherapie.